Evaluating the Effectiveness of Psychometric Tests in the Early Diagnosis of Minimal Hepatic Encephalopathy - Salkhidinovna, Bekmuradova Makhsuda; Rustamovich, Tairov Doston; Erkinovna, Khaydarova Zarrina; Abrorovna, Vafoyeva Nigora (American Journal of Biomedicine and Pharmacy, 2024)
Hepatic encephalopathy (HE) is a neuropsychiatric syndrome prevalent among patients with liver cirrhosis, often undiagnosed in its minimal form (MHE). This study aims to evaluate the effectiveness of psychometric tests in diagnosing MHE. A prospective observational study was conducted with 100 cirrhotic patients aged 35-70 years. Psychometric assessments, including the Psychometric Hepatic Encephalopathy Score (PHES), Number Connection Test-A (NCT-A), and Stroop Test, were performed at baseline and three-month intervals. Statistical analysis included descriptive statistics and correlation studies. MHE was diagnosed in 45% of patients. The PHES demonstrated a sensitivity of 84% and specificity of 90%. Significant differences in psychometric scores were observed between patients with and without MHE, with lower scores correlating with higher Child-Pugh and MELD scores. Psychometric testing is a valuable tool for early diagnosis of MHE in cirrhotic patients. Early detection can improve patient outcomes and quality of life, emphasizing the need for its integration into routine clinical practice. Future research should validate these findings in larger cohorts and assess the long-term impacts of early diagnosis and intervention.